A model to assess the cost–effectiveness of pharmacogenomics tests in chronic heart failure: the case of ivabradine. (October 2016) - Iliza, Ange C; Matteau, Alexis; Guertin, Jason R; Mitchell, Dominic; Fanton-Aita, Fiorella; Dubois, Anick; Dubé, Marie-Pierre; Tardif, Jean-Claude; LeLorier, Jacques
Pharmacogenomics (PGx) tests have the potential of improving the effectiveness of expensive new drugs by predicting the likelihood, for a particular patient, to respond to a treatment. The objective of this study was to develop a pharmacoeconomic model to determine the characteristics and the cost–effectiveness of a hypothetical PGx test, which would identify patients who are most likely to respond to an expensive treatment for chronic heart failure. For this purpose, we chose the example of ivabradine. Our results suggest that the use of a PGx test that could select a subgroup of patients to be treated with an expensive drug has the potential to provide more efficient drug utilization.